2020
DOI: 10.1002/cam4.3105
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of low‐dose apatinib in advanced gastric cancer: A real‐world study

Abstract: Apatinib has been demonstrated to be effective and safe among patients with gastric cancer failing after at least two lines chemotherapy. This study aimed to evaluate its effectiveness and safety of low‐dose apatinib for the treatment of gastric cancer in real‐world practice. We performed a prospective, multicenter observation study in a real‐world setting. Patients with advanced gastric cancer more than 18 years old were eligible and received low‐dose apatinib (500 mg or 250mg per day) therapy. The median pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Previous studies have shown that combined antiangiogenic therapy plus TMZ can significantly improve the survival rate when compared with TMZ monotherapy (20,21). In addition, the efficiency and safety of a low dose have been confirmed in other solid tumors, including nonsmall cell lung cancer, ovarian cancer, and gastric carcinoma (22)(23)(24). That is to say, to the best of our knowledge, we present the first case of low-dose apatinib combined with dose-dense TMZ for the treatment of adult brainstem glioblastoma.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that combined antiangiogenic therapy plus TMZ can significantly improve the survival rate when compared with TMZ monotherapy (20,21). In addition, the efficiency and safety of a low dose have been confirmed in other solid tumors, including nonsmall cell lung cancer, ovarian cancer, and gastric carcinoma (22)(23)(24). That is to say, to the best of our knowledge, we present the first case of low-dose apatinib combined with dose-dense TMZ for the treatment of adult brainstem glioblastoma.…”
Section: Discussionmentioning
confidence: 94%
“…Lastly, a control group for systemic chemotherapy should also be considered. Finally, it has been reported that NCT03333967[ 36 ], TAGS[ 37 ] and EPOC1201[ 38 ] can improve the prognosis of patients with advanced GC. Therefore, in future studies, it should be determined whether elemene-containing HIPEC can improve the therapeutic effects of these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that hand-foot syndrome is one of the most common side-effects of anti-VEGF treatment, which has also been suggested as a biomarker predicting the responses and prognoses of anti-VEGF treatment. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that hand-foot syndrome is one of the most common side-effects of anti-VEGF treatment, which has also been suggested as a biomarker predicting the responses and prognoses of anti-VEGF treatment. 32 The dose of apatinib in different previous clinical trials on solid tumors ranged from 500 to 750 mg once per day. 33,34 Therefore, the initial dose of apatinib in this study was 500 mg once per day.…”
Section: Discussionmentioning
confidence: 99%